PHBS LEARNING ASSISTANCE IN EFFORTS TO PREVENT STUNTING INCIDENTS AT THE GREAT PARENT (SOTH) SCHOOL OF SIDOMULYO BATU VILLAGE - say, sayuti; -, qotimah; setyowati, Susana (Penerbit Widina, Widina Media Utama, 2024)
Clean and healthy living behavior (PHBS) is a form of manifestation of healthy living orientation in individual, family and community culture, which aims to improve, maintain and protect health both physically, mentally, spiritually and socially. This clean and healthy living behavior is one of the materials at the Great Parents School in Sidomulyo village, Bayu District, Batu City. The assistance at SOTH in Sidomulyo village aims to ensure that female students (Baita's parents) understand the meaning of clean and healthy living behavior and what must be done for their toddlers to implement clean and healthy living in their family structure. By increasing the understanding of parents (students), it is hoped that female students will implement clean and healthy living behavior in their families and ultimately the incidence of illness will decrease and toddlers can grow optimally, which will ultimately reduce the incidence of stunting. The method used in Science and Technology for the Community is to provide assistance during learning to female SOTH students in Sidomulyo village. The number of students targeted was 30 SOTH students. During the implementation of the activity, the number of SOTH students who attended was 25 people, cadres, PKB. Learning activities at SOTH are carried out by dividing groups, pre-test, discussion, post-test. The purpose of the post test was to determine the increase in knowledge and abilities of female SOTH students in Sidomulyo village related to clean and healthy living behavior;